Country selection criteria practicing by TM to enter foreign country (Indonesia): a case study of Telekom Malaysia Berhad (TM) / Nor Alyda Aslinda Razak - Razak, Nor Alyda Aslinda (Faculty of Business and Management, 2011)
Foreign entry strategy becomes common mode for company to internalize in foreign market. The purpose of this research is to study the country selection criteria practicing by TM to enter foreign country (Indonesia). In this study the researcher collects the information from observation, website, and secondary data such as journal, article, annual report, and text book. This study will help Telekom Malaysia Berhad to understand the criteria practicing by TM to enter international market in the case of Indonesia. In conclusion, some recommendation and strategy have been made for TM to operate successful in foreign country. This is important to improve company performance and for the profitability of the company. From the gap the researcher has identify the criteria selection practicing by TM to enter foreign country (Indonesia).